STATE SOCIAL STANDARD IS IN THE FIELD OF SERVICE OF PHYSICAL CULTURE AND SPORT AS SOIL OF GRANT OF QUALITY ATHLETIC-SPORTING SERVICES ESTABLISHMENTS IN SYSTEM OF HIGHER EDUCATION - Орленко, Н. А.; Панченко, В. Ф.; Коротя, В. В. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2017)
In the approaches to the formation of the state social standard in the field of physical culture and sports are explored. Unsettled problems in the legal framework that prevented the formation of a qualitative system of state social standards in this sphere in the system of higher education were revealed. The updating of the content of the indicators of the quality of sports and sports services with specific requirements